Learning Tahfiz with Talaqqi Method Using Whatsapp Application - Mooh Amiin Najeed; Campbell Hakonarson; Glessner Mentch (Journal International Inspire Education Technology, 2022)
All levels of education in Indonesia during the pandemic were carried out online, including one of the Tahfidz Darul Huffaz Houses which was carried out online. Technology plays an important role in educational problems that occur during the pandemic, because technology can help the learning process remotely. However, in reality there are obstacles encountered when running the online Thafidz program, such as the lack of student motivation to participate in post-online Tahfidz learning activities. The method used in this study uses qualitative methods to describe how the description of the implementation of tahfidz Al-Qur'an learning with the online talaqqi method using the WhatsApp application, data collection is taken from interviews and field observations by observing real phenomena. The purpose of this study is to find out how Tahfidz learning is done online using the WhatsApp application, then to find out the supporting factors in Tahfidz learning with the Talaqqi method using the WhatsApp application, knowing the inhibiting factors in Tahfidz learning using the Talaqqi method through the WhatsApp application, knowing what efforts what a teacher does in dealing with problems in learning Tahfidz online with the Talaqqi method through the WhatsApp application. Based on the results of the study, it can be seen that learning Tahfidz using the WhatsApp application has had a good impact, it is very possible in the Tahfidz learning process, because by using WhatsApp Groups it has become a liaison between students and teachers to carry out Tahfidz learning normally, and allows for the memorization of Al-Quran to run smoothly. Qur'an, and muraja'ah normally.